Analytical and numerical modelling of existing RC frames with smooth rebars. (15th December 2021) - Paderno, Anthony; Pelucco, Simone; Metelli, Giovanni; Preti, Marco
Highlights: Analytical modeling of smooth rebar local behavior under cyclic axial loading. Numerical implementation of the smooth rebar stress-slip law. Assessment of the role of smooth rebar slip in the structural seismic response. Innovative modeling strategy for the non-linear response at crack location. Comparison of analytical and numerical modeling results with experimental ones. Abstract: The work refers to the seismic behaviour of existing reinforced concrete (RC) frame buildings reinforced with plain rebar. A focus on the modelling of their flexural response is proposed, to explicitly consider the effect of smooth reinforcement slip on the structural performance. Analytical stress-slip relationships for different plain rebar anchorage shape are presented, their implementation in a structural model is then suggested. The element non-linear behaviour is lumped at the element end, based on its expected rocking-like behaviour; nevertheless, the model is able to account for the deformation contribution spread along the rebar embedded length, both in the element and in the joint or foundation side. The cyclic behaviour of an anchored plain rebar is also analytically treated; however, to facilitate the representation in a numerical environment, simplified rules are proposed to simulate the effects of reversal and repeated loading. The effectiveness of the model in predicting the response of such type of buildings is proved by simulating tests on columns, beam-column joints, and an entire frame, taken from literature. The structural elastic response is well captured, as well as the energy dissipation during cycling loading. The assessed secant stiffness at yielding is found to be significantly lower with respect to the prediction obtained without the consideration of smooth bar slip; in other words, with respect to the stiffness assessed for an element with deformed reinforcement. The results are particularly significant for range of drift demand within 1.50% and help a comprehensive design and assessment of seismic retrofit of existing buildings, since the modelling approach allow a reliable prediction of the triggering of brittle mechanisms.